Reoperation for recurrent angina. - Brooks, N (1979)
Forty patients with persistent or recurrent angina after an aortocoronary bypass procedure underwent a second operation. The cause of recurrent angina, defined by angiography, was thought to be isolated graft failure in 13 patients, progression of disease in ungrafted vessels in 4, incomplete revascularisation in 2, and stenoses distal to patent grafts in 1. More than one factor was responsible in 20 patients. There was 1 early postoperative death and 3 perioperative myocardial infarctions. Thirty-four patients have been followed for more than 3 months (4 to 63 months). Of these, 17 had previously bypassed vessels regrafted and 5 are sympton free, 4 have mild angina, and 8 have severe angina. Ten patients had previously ungrafted vessels grafted and 4 are sympton free, 3 have mild angina, 2 have severe angina, and 1 is limited by breathlessness. Seven patients had a combined procedure and 4 are sympton free, 1 has mild angina, and 2 have severe angina. Reoperation can be carried out safely but the results are less satisfactory than for a primary procedure.